Contriving IT-Based Integrated Skills Approach (ITBISA) for Students’ English Proficiency and Digital Literacy Skills - Didit Kurniadi; Issy Yuliasri; Sri Wahyuni; Zulfa Sakhiyya (Qubahan Academic Journal)
Contriving technology is a trend in current TEFL in higher education. IT-Based Integrated Skills Approach (ITBISA) combines IT-based approaches with the EFL education method, ISA (Integrated Skills Approach). This study explores how ITBISA is implemented in teaching-learning and examines participants’ perspectives on its effectiveness. This study used a mixed-method research design. Data were collected through classroom observations and open-ended questionnaires and then analyzed thematically to identify key patterns. Initially, participants sourced information directly from the internet without verification. Integrating AI and other digital tools reflects a desire to adopt new technological advancements. This underscores the importance of innovative technology in creating and distributing college educational materials. Consequently, we argue that the IT-based integrated skills approach can effectively enhance students’ digital literacy and English proficiency. The findings offer a theoretical concept of how ITBISA is implemented. Figure 4 demonstrates how integrating digital tools, AI, and the Integrated Skills Approach fosters a dynamic, interactive learning environment. The findings also indicate a positive student response to ITBISA, with active participation, effective use of mobile devices, and task completion. This approach enhances instruction, making learning more efficient. ITBISA in EFL is a promising method for implementing the teaching-learning process to improve English proficiency and digital literacy.